Perceive Influence of Third-Party Logistics (3PL) Customer Satisfction Indicators and the Company’s Financial Performance - Mohamad Husaini, Badrul Zamin; Norazidah, Shamsudin; Puteri Fadzline, Muhamad Tamyez; Mohd Ghazali, Maarof (Faculty of Industrial Management, 2015)
A Third-Party Logistics (3PL) company is prominent in execute exercise relating to logistic facilities and administration, for instance transportation service and warehouse coordination. Even they are the external party or known as outsourced company, but their service offered in all industry especially product related industry is vital. A company who looks for 3PL service or also acknowledged as contract logistic service believes on the competitive advantage offered such as resource network of expertise management, cost and time effective, scalability and flexibility and continuous optimization. This research been conducted to study the perceive influence of 3PL customer satisfaction indicators that are represent by service quality, organizational effectiveness and relationship management of companies who implement 3PL service in relation to their financial performance. The objectives are to investigate the relationship between the dependent and independent variables and to identify the most significant 3PL indicator which highly influence the financial performance of 3PL implementing company. A questionaire been distributed to all six automative companies in Pekan, Pahang, however one company didn’t manage to response to the questionnaire. The collected data been processed for quantitative analysis using SPSS version 22. The results shows all selected independent variables (IV) has strong linear relationship towards dependent variable (DV) providing service quality as the most significant perceive factor of 3PL implementation towards financial performance, followed by organizational effectiveness and relationship management. It is suggested that 3PL implementation companies should put attention to the most significant factor that is service quality as their crucial criteria for 3PL outsource company selection to ensure better financial performance. On the other hand, 3PL service provider should consider the highest weightage of concern to be put for service quality, followed by organizational effectiveness and relationship management in ensuring to be nominated by their client.